Negative Adolescent Experiences And Their Influence On Psychological Well-Being In Early Adulthood - Satria Yudistira (Riviera Publishing, 2024)
Experience negative during adolescence, such as verbal abuse, neglect emotional, and conflict family, often has an impact on well-being psychological individual in adulthood early. Research This aiming For analyze influence experience negative in adolescence to welfare psychological. This study use approach qualitative with method studies case, involving five individuals mature the beginning ever experience experience negative between ages 13 to 17 years. Data obtained through interview in-depth, observation, and review literature. Research results show that dimensions objective life and acceptance self is most affected aspects, with a number of individual show difficulty in reach welfare optimal psychological findings. This emphasize importance intervention early and support social For help individual processing experience traumatic they. Research This give contribution to a greater understanding in about influence experience negative teenager to welfare psychological as well as implications for rehabilitation programs psychology and policy mental health.